Analysis of Obstacles in Implementing The Finished Banknotes Business Model (A Case Study on Banknotes Printing in Indonesia) - Saiful Bahri; Syamsul Maarif; Arif Imam Suroso; Nur Hasanah (Jurnal Organisasi dan Manajemen, 2022)
Purpose - Bank Indonesia as a central bank uses Perum Peruri as a banknote printing service provider. In general, Bank Indonesia is a consumer and a banknote paper provider that intends to change the business model from printing services to finished banknotes or end-to-end processes. Therefore, this study aimed to analyze the obstacles faced while implementing the finished banknotes business model by Perum Peruri. Methodology - A total of 9 obstacles were identified based on the literature and discussions with five experts from the banknotes printing industry, Bank Indonesia as a consumer and regulator, the Ministry of State-Owned Enterprises, and the Indonesian Printing Security Association. An interpretive structural modeling analysis was used to measure the strength of the relationship between obstacles, develop hierarchical levels, and classify and rank each obstacle. Findings - The results showed that the main obstacles included limited working capital, dependence on supplies of foreign banknotes, the complexity of their procurement, and barriers to accessing banking. These obstacles can be solved when Perum Peruri improves its capabilities and receives support from the government. Originality - This study is original and provides new knowledge about the obstacles faced by banknote printing companies when changing their business model.